The biopolitics of gender - Repo, Jemima (Oxford University Press, 2015)
This book provides a new and distinct approach to gender through the frameworks of biopolitics and genealogy, theorizing it as a historically specific apparatus of biopower. Through the use of a diverse mix of historical and contemporary documents, the book explores how the problematization of intersex infant genitalia in 1950s psychiatry propelled the emergence of the gender apparatus in order to socialize sexed individuals into the ideal productive and reproductive subjects of white, middle-class postwar America. The idea of gender was then directly appropriated from psychiatry by Anglo-American feminists during the struggle for women’s liberation, soon followed by demographers and economists concerned with the possible effects of declining fertility on Western populations. The book argues that this genealogy has critical relevance for feminist politics today, amid the deployment of gender equality as a neoliberal means of optimizing the fertility rates of ethnic Europeans and ensuring the region’s future economic growth. It shows how grasping the biopolitics of the idea of gender itself is integral to comprehending both the disappointments and challenges faced by feminist theory and politics today.
Keywords: 1900-1999; discipline; genre; histoire et politique; périodes historiques; ressource en ligne; science politique; science politique et droit; thématiques; théories féministes